HOW CHARACTER BUILDING CAN BE INTEGRATED IN THE ROLE PLAY OF THE STANDARD OF COMPETENCY THREE OF THE SOCIAL TWELVE GRADERS - Maisyaroh, Fadilah Umi (LET: Linguistics, Literature and English Teaching Journal, 2017)
Character building is currently a significant issue in education in Indonesia that has been applied in any level of learning process as an integrated moral wisdom value of the teaching materials. The objective of this activity is to contribute to the improvement of the character of Indonesian Learners through the teaching of English. A classroom observation is used in this class. The activity is started by grouping the students and giving each group a topic to be elaborated in a drama script. After the drama script is done, each group is asked to notify the interpersonal and transactional expression related to the given topic. Then, they also have to show the character building values stated on their script. After the discussion, each of the groups has to present the work in front of the class. This activity encourages students to speak, so it helps a lot in teaching speaking.